2019
DOI: 10.2217/bmm-2018-0252
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Platelet-To-Lymphocyte Ratio in Patients with Sarcoidosis

Abstract: Aim: We aimed to evaluate platelet-to-lymphocyte ratio (PLR) in patients with sarcoidosis. Methods: A total of 310 sarcoidosis patients and 220 healthy controls retrospectively were recorded in this study. Results: PLR was significantly higher in patients with sarcoidosis than in the control group, and was also significantly higher in patients with pulmonary involvement in stage 2–3–4 than in stage 1. PLR were significantly positive correlated with erythrocyte sedimentation rate. The cut-off values for PLR for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Dirican et al [9] suggested that MPV values were higher in sarcoidosis patients compared to the control group and there was no significant difference in the MPV values of the stages of sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Dirican et al [9] suggested that MPV values were higher in sarcoidosis patients compared to the control group and there was no significant difference in the MPV values of the stages of sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%
“…Mirsaeidi et al [9] reported that the cut-off value was around 3.5 while sensitivity and specificity were 50.0% and 78.0%, respectively. It was concluded in same study that NLR and PLR values of sarcoidosis patients with parenchymal involvement were significantly higher, and cut off values were 2.4 and 158, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In a retrospective study on the levels of platelet/lymphocyte ratios of patients with sarcoidosis, it was reported that there was a significant increase in PLR levels in correlation with the involvement of the lung parenchyma in patients with sarcoidosis. 10 It is thought that NLR and PLR studies with hematological parameters will provide a great advantage in the diagnosis of sarcoidosis, which is mainly manifested by lung involvement. In 2020, in a study by Korkmaz et al, it was found that in sarcoidosis patients, PLR and NLR levels were weakly positively correlated with CRP, while there was a moderate positive correlation between NLR levels and blood CD4/CD8 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In various clinical situations, neutrophil/lymphocyte (NLR) and platelet/lymphocyte (PLR) ratios are increased in malignancies, respiratory diseases, cardiovascular diseases, and many inflammatory diseases, and it has been shown that high levels are associated with the poor prognosis and low levels are associated with the good prognosis. 4 Neutrophils play a role in the pathogenesis of many important inflammatory diseases. Neutrophils perform their antimicrobial activities by regulating tissue factor production and thrombocyte activation through oxygen radicals.…”
Section: Introductionmentioning
confidence: 99%